PENDEKATAN TEOLOGIS ATAS AYAT KHURU - Moh Yusuf (IAIN Ponorogo, 2017)
Abstract: Da'wah Khuru>j fi> Sabi>lilla>h Jama>'ah Tabli>gh is a da'wah that is still considered peculiar amongMuslims. It was introduced by Maulana Ilyas the founder of Jama>'ah Tabli>gh and it became the hallmark and identity of the group of da'wah further. Theologically, it is derived from verse 110 in surah A<li 'Imra>n. The khuru>j is the derivation of the phrase